Consumer awareness and sweetener consumption habits of dietetics students - Jaruga-Sękowska, Sylwia; Staśkiewicz, Wiktoria; Woźniak-Holecka, Joanna; Wanat-Kańtoch , Gabriela; Kardas, Marek; Wójcicka, Agata (Journal of Education, Health and Sport, 2022)
Introduction. The incidence of obesity has continued to rise over the years, a problem that is driving increased consumer interest in agents that can replace sucrose. Sweet taste is linked to feelings of pleasure and happiness. For this reason, among others, substances that are alternatives to sugar have received increasing attention over the past few years. The aim of the study was to assess consumer awareness and sweetener consumption habits of dietetics students. Material and methods. The study included 201 participants aged 18-27 years studying nutrition. Nutritional status was assessed using the Body Mass Index (BMI). A proprietary validated survey questionnaire was used to assess consumer awareness and assess eating habits Results. The subjects' nutritional status was examined by assessing their BMI. Most of the respondents had a BMI described as normal. Respondents mostly sometimes focused attention on the amount of calories consumed during the day, with 64.68% (N=130) of respondents giving this answer. Respondents cited health benefits (28.36%; N=57), energy value (20.40%; N=41), and taste (17.91%; N=36) as the most influential factor in choosing a particular sweetener. The study group's nutritional knowledge of sweeteners was unsatisfactory. Conclusions. Dietetics students' knowledge of sweeteners is alarmingly low. Most of the respondents had a BMI described as normal. In view of the low level of knowledge of the respondents, additional measures should be introduced resulting in an increase in the awareness of students in the described field, for example, increasing the number of lectures covering the above topics.